2018
DOI: 10.1186/s13034-018-0255-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychological Suzhi and social anxiety among Chinese adolescents: the mediating role of self-esteem and sense of security

Abstract: BackgroundHigh incidence and morbidity rates are found among adolescents with social anxiety disorder, a severe and harmful form of social phobia. Extensive research has been conducted to uncover the underlying psychological factors associated with the development and continuation of this disorder. Previous research has focused on single individual difference variables such as personality, cognition, or emotion; thus, the effect of an individual’s full psychological profile on social anxiety has rarely been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
(38 reference statements)
1
17
0
1
Order By: Relevance
“…We further observed that HPS showed lower state anxiety than LPS. This is consistent with findings in which psychological suzhi was associated with less negative emotional experiences (Nie, Yang, et al., 2020; Pan et al., 2018). The trait‐congruent effects propose that individuals prefer to process the information in alignment with their own traits and avoid information that is not, which provides one possible explanation (Bargh et al., 1988).…”
Section: Resultssupporting
confidence: 92%
“…We further observed that HPS showed lower state anxiety than LPS. This is consistent with findings in which psychological suzhi was associated with less negative emotional experiences (Nie, Yang, et al., 2020; Pan et al., 2018). The trait‐congruent effects propose that individuals prefer to process the information in alignment with their own traits and avoid information that is not, which provides one possible explanation (Bargh et al., 1988).…”
Section: Resultssupporting
confidence: 92%
“…Researchers stated that changes in adulthood personality patterns might be related to childhood experiences (Eisenberg et al, 2014 ; Fletcher & Schurer, 2017 ). Children who gain emotional confidence in the family system during childhood may be happier and less prone to experiencing psychological problems thanks to a safe and supportive environment and gaining positive qualities such as empathy (Shoshani et al, 2021 ) and self-esteem (Pan et al, 2018 ). It was found that having problems gaining emotional confidence was associated with negative situations such as aggression and anxiety (Bergman et al, 2014 ) and depression (Cummings et al, 2013 ).…”
Section: Emotional Security Emotional Reactivity Forgiveness and Happ...mentioning
confidence: 99%
“…Pojem suzhi také často používá vláda, když mluví o loajalitě a morálce občanů (Wang, Lamond, Worm, Gao & Yang, 2014). Vysoké suzhi u čínských adolescentů snižuje sociální úzkost, protože přispívá k vyššímu sebehodnocení, které dále zvyšuje pocit bezpečí, což přispívá k nízké úzkosti (Pan, Zhang, Hu & Pan, 2018).…”
Section: Suzhi a Baounclassified